Faktor – Faktor Yang Mempengaruhi Prestasi Belajar Mahasiswa Politeknik Negeri Samarinda Dan Implikasi Terhadap Waktu Tunggu Kerja Di Industri - Tandi Kadang; Muhtar Sehe; Nita Harnitalia (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2020)
This Research aim was to analyze how much the influence of the Lecturer Quality, Teaching Facilities, Service Quality and Learning Achievement on Waiting Time. The independent variables in the study were Lecturer Quality, Teaching Facilities, and Service Quality, while Learning Achievement as Intervening variable and Waiting Time as the dependent variable. This research used 85 respondents and it was conducted at Samarinda State Polytechnic. This study used SEM (Structural Equation Modeling) analysis tools with the help of PLS (Partial Least Square) software version 3.20 and SPSS version 24.The results of this study stated that the quality of lecturers had a significant positive effect on Learning Achievement, then teaching facilities had a significant positive effect on learning achievement,then the quality of service had a significant positive effect on learning achievement, then the quality of lecturers had a significant positive effect on Working Waiting Time, then Teaching Facilities had no significant positive effect on Working Waiting Time, then Service Quality was not a significant positive effect on Working Waiting Time, then Learning Achievement had a significant positive effect on Work Waiting Time.